Dentist Interpersonal Communication Relationships Seen From The Aspects of Openness and Empathy with Patient Satisfaction in Kendari City Health Center - Febrina Nineti, Ilfen; Risky, Sartini; Kamalia, La Ode (Magister Kesehatan Universitas Mandala Waluya, 2023)
Backgrounds: The Indonesian Doctor Competency Standards state that doctors must be able to communicate effectively with their patients. Dentists are required to master communication skills so that ambiguous communication does not occur and there is no gap between the patient's expectations and the reality obtained by the patient. This study aims to analyze the relationship between dentist interpersonal communication and patient satisfaction at the Kendari City Health Center. Methods: The research method uses quantitative, using a cross sectional study approach. The population was 24,960 people and the total sample was 96 divided into each health center. Results:The chi-square test obtained p value (0.001) and X2hit (10.293), because the p value (0.001) < α (0.05) and the X2hit value (10.293) > p value (0.002) and X2hit (11.293), because the p value (0.002) < α (0.05) and the X2hit value (11.293) > teeth at the Kendari City Health Center. Conclusion: Health center that have good service, namely by providing facilities that will have an impact on clients and the Health center workforce, one of which is doctors.